Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon - Sáfián, Szabolcs; Tropek, Robert (Zootaxa, 2016)
A field survey of Mount Cameroon, South-West Province, Cameroon, revealed two butterfly species new to science. Lepidochrysops liberti sp. nov. (Lycaenidae) flies in the extensive mosaic of natural clearings in sub-montane forest above 1100 m a.s.l., whereas Ceratrichia fako sp. nov. (Hesperiidae) locally inhabits the forested narrow gullies in the same vegetation zone. Observations on the habitat and behaviour of both species are also presented.
Keywords: lesy; Female; Animal Structures; Animal Distribution; Animals; Cameroon; motýli; ženské pohlaví; mužské pohlaví; Butterflies; rozšíření zvířat; Male; zvířata; anatomické struktury zvířat; Forests; Kamerun